Pelvic Floor Fractures in 55 Dogs and 39 Cats: CT and X- Ray Findings - Sadan, M.A; Amort, K; Kramer, M (International Journal of Veterinary Sciences Research, 2016)
Radiographic examination of the pelvis is the standard diagnostic test for evaluating dogs with suspected pelvic trauma, but because of the complexity of many pelvic floor fractures and the superimposition of bony structures, a precise description of the injury can be difficult to obtain from standard radiographs. Computed tomography (CT) imaging is an important component in the pre-operative assessment and management of pelvic fractures in humans and small animal. The objective of this study was to investigate the benefits of radiographic and CT images in the diagnosis of pelvic floor fractures in dogs and cats. Our hypothesis was that CT would detect the different types of pelvic floor fracture than radiographic examination of these fractures. Radiographic examination and CT scan of 94 traumatized cases of canine and feline pelvic floor fractures were evaluated, where CT images and radiographic assessments were performed on each case. Radiographs and CT images were reviewed on separate occasions and fracture assessments were evaluated. Of the examined 55 dogs and 39 cats, unilateral ischium fractures were the most common detectable fractures in dogs (67.92%) and in cats (72.41%) (Table 1). Different fracture lines (transverse, longitudinal and oblique fractures lines) of ischium and pubic bones were observed, they were more clear in the computed tomography than in plain radiographs. Pelvic floor fractures were associated with unilateral sacroiliac joint luxation, bilateral sacroiliac joint luxation and femur luxation and fractures of sacrum, ilium, acetabulum, femur and tibia (Table 2).